Influence of Ageing and Regional Differences on Draught Performance of Umblachery Cattle - M, Kousalya Devi; SMK, Karthickeyan; R, Venkataramanan; SN, Sivaselvam; KG, Tirumurugaan (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
An attempt was made to assess the effects of aging, regional differences, and draught load applied on draught potential of Umblachery  cattle, an important draught breed of South India. Age had a highly significant effect (p
Keywords: Aging; Optimum draft load; Regional variations; Umblachery